" The Indian Ocean in Eurasian and African World-Systems Before the Sixteenth Century " - (:unkn) unknown (My University, 2005)
The rise of towns and states and the expansion of exchange networks have resulted in the formation of various world-systems in Asia, Africa and Europe since the 4th millenium BC. In the 1st century AD, exchanges transformed the Indian ocean into a unified and stratified space, embedded in a Eurasian and African world-system. This system evolved until the 16th century through four cycles which saw growing integration of its parts, demographic rise, a general growth of commerce and production, and the simultaneous development of hierarchical relations between cores, semi-peripheries and peripheries within an international division of labor. This early history sheds light on the period that would follow, which saw the emergence of the modern capitalist world-system, and perhaps also provides some hints as to the possible futures of the system.
Keywords: African Research